2014
DOI: 10.1073/pnas.1412323111
|View full text |Cite
|
Sign up to set email alerts
|

Cyst formation following disruption of intracellular calcium signaling

Abstract: Mutations in polycystin 1 and 2 (PC1 and PC2) cause the common genetic kidney disorder autosomal dominant polycystic kidney disease (ADPKD). It is unknown how these mutations result in renal cysts, but dysregulation of calcium (Ca 2+ ) signaling is a known consequence of PC2 mutations. PC2 functions as a Ca 2+ -activated Ca 2+ channel of the endoplasmic reticulum. We hypothesize that Ca 2+ signaling through PC2, or other intracellular Ca 2+ channels such as the inositol 1,4,5-trisphosphate receptor (InsP3R), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 67 publications
6
31
0
Order By: Relevance
“…The abnormal proliferation and apoptosis of cystic epithelial cells are hallmarks of ADPKD . Consistent with previous studies , we found that although rapamycin did not affect apoptosis in the cyst‐lining epithelia of the Vil ‐Cre; Pkd2 f3/f3 kidney (Fig.…”
Section: Resultssupporting
confidence: 91%
“…The abnormal proliferation and apoptosis of cystic epithelial cells are hallmarks of ADPKD . Consistent with previous studies , we found that although rapamycin did not affect apoptosis in the cyst‐lining epithelia of the Vil ‐Cre; Pkd2 f3/f3 kidney (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Notably, chimeric mice lacking endogenous PDGFRβ display renal cysts and glomerulosclerosis (Klinghoffer et al, 2001), phenotypes associated with defective intracellular Ca 2+ signaling (Kuo et al, 2014) and ciliopathies (Hildebrandt et al, 2011). Because PDGFRα D842V and AURKA expression is linked to GIST (Corless et al, 2011;Yeh et al, 2014), and precursors of GIST cells are ciliated (Castiella et al, 2013), it will be interesting to study whether GIST cells display ciliary defects that are caused by elevated PLCγ and AURKA activity.…”
Section: Discussionmentioning
confidence: 99%
“…60 Interestingly, knockdown of IP3R1 or IP3R3, like the knockdown of PC2, induces cell proliferation, apoptosis, and cyst formation in a collagen-matrigel three-dimensional culture system using pig kidney epithelial (LLC-PK) cells. 70 Several studies have shown that store operated calcium entry is reduced in PC2 defective cells 34,51,55,57,71 and it has been suggested that the interaction between STIM1 (a transmembrane sensor for calcium concentration in the endoplasmic reticulum lumen) and ORAi (the pore-forming unit of a plasma membrane channel that permits calcium entry in response to a reduction in the endoplasmic reticulum calcium concentration) is uncoupled in these cells. 71 Although PC2 is mostly located in the endoplasmic/sarcoplasmic reticulum membrane, truncated forms lacking the endoplasmic/sarcoplasmic reticulum retention domain translocate to the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%